THEORETICAL AND PRACTICAL STUDY IN INFORMATION LITERACY AS A FACTOR OF INTERACTION BETWEEN THE INFORMATION SCIENCE AND HISTORY OF SCIENCE WITH QUALITATIVE APPROACHES - Rosetto, Marcia; Baptista Belluzzo, Regina Celia [UNESP] (Inst Fed Education, Science & Technology Of Goias, Campus Inhumas, 2016)
The purpose of this research was to identify Information Literacy from the point of view of Scientific Literacy as an interaction factor between Information Science and History of Science, when considering the issues of access and use of documents and information sources contributing to the consolidation of evaluation criteria for the purpose of transposition and applicability of these principles by researchers in the field of History of Science, who are known as senders and receivers of information as well as creators of scientific knowledge. By means of methodological procedures involving literature research, establishment and transposition of basic standards and Information Literacy performance indicators for the access and use of documents and information sources, case studies compiled from field researches, including desk research on the Simao Mathias Center for Studies in the History of Science - PUC/SP (CESIMA), workshop and interviews with researchers from the Center, it was possible to collect data and reach conclusions that reflect the relationship between theory and practice, having Information Literacy as the main factor, as initially proposed by the research.
Keywords: Qualitative research; Information Literacy; Scientific Literacy; History of Science; Information Science